High‐Frequency Wave Generation in Magnetotail Reconnection: Linear Dispersion Analysis. Issue 8 (23rd April 2019) - Burch, J.L.; Dokgo, K.; Hwang, K.J.; Torbert, R.B.; Graham, D.B.; Webster, J.M.; Ergun, R.E.; Giles, B.L.; Allen, R.C.; Chen, L.‐J.; Wang, S.; Genestreti, K.J.; et al.
Abstract: Plasma and wave measurements from the NASA Magnetospheric Multiscale mission are presented for magnetotail reconnection events on 3 July and 11 July 2017. Linear dispersion analyses were performed using distribution functions comprising up to six drifting bi‐Maxwellian distributions. In both events electron crescent‐shaped distributions are shown to be responsible for upper hybrid waves near the X‐line. In an adjacent location within the 3 July event a monodirectional field‐aligned electron beam drove parallel‐propagating beam‐mode waves. In the 11 July event an electron distribution consisting of a drifting core and two crescents was shown to generate upper‐hybrid and beam‐mode waves at three different frequencies, explaining the observed broadband waves. Multiple harmonics of the upper hybrid waves were observed but cannot be explained by the linear dispersion analysis since they result from nonlinear beam interactions. Plain Language Summary: Magnetic reconnection is a process that occurs throughout the universe in ionized gases (plasmas) containing embedded magnetic fields. This process converts magnetic energy to electron and ion energy, causing phenomena such as solar flares and auroras. The NASA Magnetospheric Multiscale mission has shown that in magnetic reconnection regions there are intense electric field oscillations or waves and that electrons form crescent and beam‐like populations propagating both along and perpendicular to the magnetic field. This study shows that the observed electron populations are responsible for high‐frequency waves including their propagation directions and frequency ranges. Key Points: Electron crescent‐shaped distributions produce upper hybrid waves in magnetotail reconnection events Field‐aligned electron beams generate parallel electrostatic waves through the beam‐mode Multiple crescent and convecting core distributions act together to produce broad frequency spectra as observed by MMS